“Head-to-Toe” Lipid Properties Govern the Binding and Cargo Transfer of High-Density Lipoprotein - Florian Weber; Markus Axmann; Erdinc Sezgin; Mariana Amaro; Taras Sych; Armin Hochreiner; Martin Hof; Gerhard J. Schütz; Herbert Stangl; Birgit Plochberger (Membranes)
The viscoelastic properties of biological membranes are crucial in controlling cellular functions and are determined primarily by the lipids’ composition and structure. This work studies these properties by varying the structure of the constituting lipids in order to influence their interaction with high-density lipoprotein (HDL) particles. Various fluorescence-based techniques were applied to study lipid domains, membrane order, and the overall lateral as well as the molecule–internal glycerol region mobility in HDL–membrane interactions (i.e., binding and/or cargo transfer). The analysis of interactions with HDL particles and various lipid phases revealed that both fully fluid and some gel-phase lipids preferentially interact with HDL particles, although differences were observed in protein binding and cargo exchange. Both interactions were reduced with ordered lipid mixtures containing cholesterol. To investigate the mechanism, membranes were prepared from single-lipid components, enabling step-by-step modification of the lipid building blocks. On a biophysical level, the different mixtures displayed varying stiffness, fluidity, and hydrogen bond network changes. Increased glycerol mobility and a strengthened hydrogen bond network enhanced anchoring interactions, while fluid membranes with a reduced water network facilitated cargo transfer. In summary, the data indicate that different lipid classes are involved depending on the type of interaction, whether anchoring or cargo transfer.